2016
DOI: 10.1177/107327481602300411
|View full text |Cite
|
Sign up to set email alerts
|

Geographical Factors Associated with Health Disparities in Prostate Cancer

Abstract: Disparities in prostate cancer are common and persistent, and notable differences in treatment are observable across racial and socioeconomic strata. Geographical analysis provides additional information about where disparate groups live and also helps to map access to care. This information can be used by public health officials, health-systems administrators, clinicians, and policymakers to better understand and respond to geographical barriers that contribute to disparities in care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 60 publications
0
8
0
Order By: Relevance
“…Our findings were consistent with two earlier systematic reviews on variations in prostate cancer incidence and mortality by rurality (5) and survival by socioeconomic disadvantage (7), respectively. Two earlier reviews also found persistent geographical disparities across a range of prostate cancer outcomes in the USA (201) and worldwide (4). None of these previous reviews critically assessed studies or included the one-third (58 of 169) of articles included in this review published since 2014.…”
Section: Discussionmentioning
confidence: 92%
“…Our findings were consistent with two earlier systematic reviews on variations in prostate cancer incidence and mortality by rurality (5) and survival by socioeconomic disadvantage (7), respectively. Two earlier reviews also found persistent geographical disparities across a range of prostate cancer outcomes in the USA (201) and worldwide (4). None of these previous reviews critically assessed studies or included the one-third (58 of 169) of articles included in this review published since 2014.…”
Section: Discussionmentioning
confidence: 92%
“…However, as noted in previous studies socioeconomic status and educational level have been found to negatively impact prostate cancer screening and overall cancer outcomes. 1,8,9,30 …”
Section: Discussionmentioning
confidence: 99%
“…Being AA, older, and having a positive family history of PCa are all associated with increased risk of a PCa diagnosis and death. 7–8 Beyond these risk factors, Gilbert et al 8 concluded that men of lower social status and educational level were also less likely to participate in PCa screening.…”
Section: Prostate Cancermentioning
confidence: 99%
“…However, certain geographic variations in quality of care linked to racial disparities are still undeniable. 3 In addition, Kaur et al most recently warned that improvements in survival disparities in the prostate-specific antigen era might be smaller than observed as they affect both African American and white American men equally. 4 Such "artifacts of screening" need to be taken into account when interpreting current prostate cancer survival data.…”
Section: Editorial Commentmentioning
confidence: 99%
“…In summary, these observations show a shift from the generally accepted paradigm of worse prostate cancer survival in African American men. However, certain geographic variations in quality of care linked to racial disparities are still undeniable . In addition, Kaur et al .…”
mentioning
confidence: 99%